SOCIAL AND CULTURAL DIMENSIONS IN ENGLISH LANGUAGE LEARNING: THEIR ROLE IN THE DEVELOPMENT OF SECOND LANGUAGE SKILLS - Manurung, Lastri Wahyuni; Saragi, Christina Natalina; Lumbantobing, Febrina S.L.; Simbolon, Desi.A.R (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2025)
This study investigates the influence of social and cultural factors on the acquisition of English-speaking skills among university students in Indonesia. While previous research has highlighted the importance of cognitive and instructional factors in second language acquisition, relatively few studies have examined the broader sociocultural context of English learning in the Indonesian EFL setting. Using a mixed-methods design, this research involved 33 sixth-semester students of the English Education Program at Universitas HKBP Nommensen, Medan, comprising 8 males and 25 females from Batak Toba and Nias ethnic backgrounds. Data were collected through speaking tests, semi-structured interviews, questionnaires, and classroom observations. The findings reveal that social background factors—including socioeconomic status, access to English courses, and family environment—affect students’ speaking proficiency. Additionally, cultural exposure, including engagement with English media and intercultural experiences, plays a crucial role in enhancing fluency, confidence, and communicative competence. The study concludes that language learning is inseparable from its sociocultural context, emphasizing the need for culturally responsive pedagogy in Indonesian higher education.